2017
DOI: 10.1111/1750-3841.13954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Vitro Digestion on the Total Antioxidant Capacity and Phenolic Content of 3 Species of Oregano (Hedeoma patens, Lippia graveolens, Lippia palmeri)

Abstract: Oregano is a rich source of polyphenols that have shown bioactive properties like anti-inflammatory potential. However, little is known of the gastrointestinal fate of oregano polyphenols which is imperative to fully understand its bioaccessibility. Our results are important to develop new administration strategies which could help protect the antioxidant and anti-inflammatory potential and bioaccessibility of such compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 34 publications
(49 reference statements)
0
31
1
Order By: Relevance
“…Studies by Gutiérrez‐Grijalva et al . on Hedeoma patens , Lippia graveolens , and Lippia palmeri described digestion having significant positive or negative influences on phenolics and flavonoids contents and antioxidant activities (RP, DPPH, ORAC, ABTS), depending on the stage of digestion and the antioxidant assay; however, the content of individual phenolic compounds for each step was negatively affected …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies by Gutiérrez‐Grijalva et al . on Hedeoma patens , Lippia graveolens , and Lippia palmeri described digestion having significant positive or negative influences on phenolics and flavonoids contents and antioxidant activities (RP, DPPH, ORAC, ABTS), depending on the stage of digestion and the antioxidant assay; however, the content of individual phenolic compounds for each step was negatively affected …”
Section: Discussionmentioning
confidence: 99%
“…23,24,27 Although analysis of bioactive compounds in CE is commonly used for predicting the biological significance of plant materials, some previous work indicated that the digestion process leads to changes in phenolic profiles and in their activity. 17,[28][29][30] In this study, therefore, the in vitro digestion model was applied to determine potential bioaccessibility and activity phytochemicals and to gain a better understanding of the pro-health potential of Greek oregano affected by nitrogen fertilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the effects of in vitro simulated digestion on the phenolic compounds and their antioxidant activity have found that the digestion of polyphenols in the gastrointestinal tract is affected by gastrointestinal enzymes, the pH of the internal environment, inorganic salts, and other factors, all of which can alter the antioxidant activity of polyphenols (Gutiérrez‐Grijalva, Angulo‐Escalante, León‐Félix, & Heredia, ; Ozdal, Capanoglu, & Altay, ). Similarly, the sample drying method affects the release of phenolic compounds (Ji et al, ).…”
Section: Introductionmentioning
confidence: 99%